La TDC frente a conductas que atentan la vida de pacientes con rasgos/diagnóstico TLP - Rebata Chavez, Micaela Denisse (2022)
Borderline personality disorder shows as a diagnostic feature suicidal behavior being this the second leading cause of death worldwide with ages 15 - 29 years evidencing that more than 800 000 people take their own lives per year (Boggiano & Gagliesi, 2018). Likewise, it is estimated that between 10-40% of people who commit the suicidal act have previously engaged in self-injurious behaviors. (Boggiano & Gagliesi, 2018). Therefore, this research aimed to evaluate the effectiveness of dialectical behavior therapy (DBT) on life-threatening behaviors (self-injury and suicidal ideation/intention) in people with BPD traits/diagnosis. The methodology used was a review applied under the PRISMA guidelines (Urrutia & Bonfill, 2013), specifying the eligibility criteria, search strategies and flowchart. The results allow pointing out that the therapy evidences to be effective against life-threatening behaviors in people with BPD traits/diagnosis. The results of the ten investigations reviewed were analyzed and dialectical behavior therapy was found to be effective in reducing self-injurious and suicidal behaviors. A shorter, but effective temporary modality of intervention of comprehensive therapy is suggested.